Structure in space of hyperplane element with special metrics - Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2010)
The present work analyses intrinsic antiquaternionic structures of metric hyperplane elements. Spaces of metric hyperplane elements is Cartan space generalisation. The given spaces are cotangent bundle, where metrics is described by way of symmetric tensor. The present work analyses situation when metric tensor has specific form, as it done by work [5]. It has been proved that in such metric space treeparameter intrinsic antiquaternionic structure families exist, associated affine connections with structures have been found.